Assessment of arrhythmias in 50 patients of ST-elevation myocardial infarction after thrombolysis: a 24 hour Holter study - Rajhans, Rishi; Narayanan, M. (International Journal of Advances in Medicine, 2017)
Background: Acute coronary syndrome represents a global epidemic. The purpose of this study was to evaluate the incidence of cardiac arrhythmias in acute myocardial infarction (AMI) in the first 24 hours of hospitalization post thrombolysis. Methods: 50 patients of AMI satisfying the inclusion criteria were included for this observational study. Philips Digitrak Holter was attached to the patient’s chest for 24 hours and arrhythmias were noted. Results: In the study group 70% of cases were males, rest 30% females. Maximum incidence of AMI was seen between 4th and 7th decade of life. Incidence of diabetes and hypertension were 54% and 66% respectively either alone or in combination. Overall incidence of anterior wall was higher 56% than inferior wall which was 44%. Sinus tachycardia was seen in 54% of cases with higher incidence in anterior wall MI. Among the reperfusion arrhythmias incidence of frequent VPCs was highest with 66% followed by AIVR (42%) and NSVT (30%). AF was found in 3 cases i.e. 6% of which one died. One patient had VF to which she succumbed. Conclusions: It is a matter of debate whether arrhythmias being so common in AMI, should be considered under clinical spectrum or complication of AMI. An increasing belief that less serious arrhythmias may serve as a warning sign for potentially life threatening arrhythmias and timely intervention by drugs, D.C. shock or pacemakers can prevent mortality in these sets of patients.